2013
DOI: 10.1667/rr3198.1
|View full text |Cite
|
Sign up to set email alerts
|

Functional Proteomics Analysis to Study ATM Dependent Signaling in Response to Ionizing Radiation

Abstract: Ataxia telangiectasia (AT) is a human genetic disease characterized by radiation sensitivity, impaired neuronal development and predisposition to cancer. Using a genetically defined model cell system consisting of cells expressing a kinase dead or a kinase proficient ATM gene product, we previously reported systemic alterations in major metabolic pathways that translate at the gene expression, protein and small molecule metabolite levels. Here, we report ionizing radiation induced stress response signaling ari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…More directly, Ephrin A, ERBB4, and Neuregulins have been identified for their potential roles as radiation-associated carcinogenesis biomarkers. Cheema et al 46 showed that the Ephrin signaling pathway responds to irradiation in an ATM-dependent manner. ERBB4 is part of the epidermal growth factor receptor pathway that is activated by radiation, resulting in downstream effects on MAPK and cell proliferation 47 .…”
Section: Discussionmentioning
confidence: 99%
“…More directly, Ephrin A, ERBB4, and Neuregulins have been identified for their potential roles as radiation-associated carcinogenesis biomarkers. Cheema et al 46 showed that the Ephrin signaling pathway responds to irradiation in an ATM-dependent manner. ERBB4 is part of the epidermal growth factor receptor pathway that is activated by radiation, resulting in downstream effects on MAPK and cell proliferation 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides examining tumor microenvironment, other efforts are made to discover biomarkers useful for predicting outcomes [46][47][48][49][50][51][52][53]. However, the results of these studies are yet of insufficient reliability to be employed in the clinical setting.…”
Section: Proteome Analysis As a Radiation Therapy Predictormentioning
confidence: 99%
“…These signaling pathways are governed by translational and post-translational events, leading to the need for analysis of differential protein levels. Since the primary focus has been on the radiation stress response, global changes in the proteome were determined by comparing 2-D gel patterns with and without radiation exposure [11]. …”
Section: 1 Introductionmentioning
confidence: 99%
“…Pathways showing significant perturbations included purine, pyrimidine and aminosugars metabolism (Fig. 15.4) [11]. …”
Section: 1 Introductionmentioning
confidence: 99%
See 1 more Smart Citation